Turn-Taking in Daebak Show Podcast Season 3 (2023) - Atika Nurul Aulia; Cristina Christina (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2024)
This study conducted to analyze: (1) the turn-taking strategies used by the host to the guest stars, (2) the functions the use of turn-taking in the Daebak Show Season 3 podcast. This study used qualitative method to analyze the problem statements. The methods collecting data includes watching, transcribing, identifying, classifying and selecting data. The technique for analyzing data includes displaying, explaining, and concluding. The theories and approaches utilized by the researcher include Pragmatics, Conversation Analysis, and Turn-Taking. The findings of this study reveal that (1) three different types of strategies were identified in the podcast conversations are taking the turn, holding the turn, and yielding the turn, (2) The function that used in Daebak Show Season 3 are starting up, taking over, interrupting, filled pause and verbal fillers, silent pause, lexical repetition, new start, prompting and appealing strategy.